2019
DOI: 10.1111/dom.13845
|View full text |Cite
|
Sign up to set email alerts
|

Impact of technology on glycaemic control in type 2 diabetes: A meta‐analysis of randomized trials on continuous glucose monitoring and continuous subcutaneous insulin infusion

Abstract: Aim To conduct a meta‐analysis to assess the effect of continuous subcutaneous insulin infusion (CSII), continuous glucose monitoring (CGM), and the combination of the two, on glycaemic control in type 2 diabetes. Materials and methods The analysis included randomized clinical trials comparing CSII with multiple daily injections (MDI) in people with type 2 diabetes, as well as studies comparing CGM or flash glucose monitoring (FGM) with self‐monitoring of blood glucose (SMBG), with a duration of at least 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 24 publications
0
83
0
2
Order By: Relevance
“…Some reviews could not detect beneficial effects of CSII therapy for patients with T2DM 7 or concluded similar outcomes of CSII and MDI. [8][9][10][11] Other reviews, however, reported better glycemic control in people with long-standing diabetes and poor glycemic control at baseline through CSII compared with MDI. [12][13][14] Since most trials do not show a consistent body of evidence, this conclusion mainly refers to the results of the OpT2mise study.…”
mentioning
confidence: 99%
“…Some reviews could not detect beneficial effects of CSII therapy for patients with T2DM 7 or concluded similar outcomes of CSII and MDI. [8][9][10][11] Other reviews, however, reported better glycemic control in people with long-standing diabetes and poor glycemic control at baseline through CSII compared with MDI. [12][13][14] Since most trials do not show a consistent body of evidence, this conclusion mainly refers to the results of the OpT2mise study.…”
mentioning
confidence: 99%
“…Similarly, the HypoDE trial showed that, in comparison to usual care, the use of Dexcom‐based CGM resulted in a significant reduction in hypoglycemic events in patients with impaired hypoglycemia‐awareness and a history of severe hypoglycemia 20 . Several meta‐analyses of RCTs in patients with type 1 and 2 diabetes have shown that CGM provides greater reduction in HbA1c values with less hypoglycemia as compared with usual care 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…9 A meta-analysis of five studies identified no difference in A1C reduction between CSII and MDI among patients with T2DM. 10 In another meta-analysis of five studies, there was a marginal reduction in A1C and insulin requirements in patients with T2DM who were managed with CSII, compared with MDI. 11 In addition, there was no difference in weight among patients receiving CSII or MDI.…”
Section: Insulin Pump Management In the Outpatient Settingmentioning
confidence: 99%